Research of bacillus cereus and sanitary quality in samples of cooked rice gathered in different establishments of Puebla city, Mexico - Tejeda-Trujillo, Fausto (Universidad Autónoma de Tamaulipas, 2013)
Bacillus cereus is recognized as a pathogenic agent causative of food poisonings. There have been outbreaks associated with the consumption of rice contaminated with this bacterium. It is one of the few pathogens with capacity to spoil the food. An outbreak occurred in 1994, in the state of Puebla, México, people infected claimed to have consumed “acid rice”. The sanitary quality was determined on 50 samples of cooked rice gathered in different establishments of the Puebla, City (homes, diners, tortilla shops and supermarkets). The count of B. cereus was realized on MYP agar (mannitol-egg yolk-polymyxin B agar), mesophilic aerobic bacteria and coliforms bacteria recounts were performed following the official methodology. Results obtained showed mesophilic aerobic bacteria high counts (> 106 CFU/g) in 22 % of the samples and in 44 % coliforms bacteria presence was demonstrated. In 10 % of the samples B. cereus was recuperated. Even with figures considered far below those of health risk, if stored in conditions of temperature abuse, as It often happens In the sampled sites contaminated rice still represents a health risk for the consumer.